Journal Info (Law, State and Telecommunications Review, 2020)
Editor-in-Chief: Prof. Marcio Iorio Aranha (University of Brasilia - BRAZIL)Editorial Board: Prof. André Rossi (Utah Valley University - USA), Prof. Ana Frazao (Universidade de Brasilia - BRAZIL), Prof. Clara Luz Alvarez (Universidad Panamericana - MEXICO), Prof. Diego Cardona (Universidad de Rosario - COLOMBIA), Prof. Flavia M. S. Oliveira (Universidade de Brasilia - BRAZIL) Prof. Francisco Sierra Caballero (Universidad de Sevilla - SPAIN), Prof. Fabio Bassan (Universitá degli Studi Roma Tre - ITALIA), Prof. Hernán Galperin (University of Southern California - USA), Prof. Jerônimo Siqueira Tybusch (Universidade Federal de Santa Maria - BRAZIL), Prof. João Alberto de Oliveira Lima (Universidade do Legislativo Brasileiro - BRAZIL), Prof. Judith Mariscal (CIDE - MEXICO), Prof. Liliana Ruiz de Alonso (Universidad San Martín de Porres - PERU), Prof. Lucas Sierra (Universidad de Chile - CHILE), Prof. Luís Fernando Ramos Molinaro (Universidade de Brasília - BRAZIL), Prof. Murilo César Ramos (Universidade de Brasília - BRAZIL), Prof. Raúl Katz (Columbia University - USA), Prof. Roberto Muñoz (Universidad Técnica - CHILE).ISSN: 1984-9729EISSN: 1984-8161Periodicity: two annual issues on May and October uninterrupted since May 2009.Mission/Scope/Focus: http://periodicos.unb.br/index.php/RDET/aboutSubmission process: authors are requested to submit their papers following the instructions at http://periodicos.unb.br/index.php/RDET/about/submissions. The journal adopts the double-blind peer review process.Archiving policy: LOCKSS, DOAJ and Brazil’s Senate Library.Indexation: Scopus (Elsevier); EBSCOhost research databases (EBSCO Publishing Inc.); Gale Group; AE Global Index; OAI (Open Archives Initiative) - DOAJ (Directory of Open Access Journals); WorldCat; Google Scholar; The European Library; CIEPS (Centre International d’Enregistrement des Publications en Série; SEER/IBICT.Permanent Web Identifier: LexML and DOI.